The discretionary powers of the Yang di-Pertuan Agong: its significance to the workability of Malaysian government / Faez Razak, Hazralika Hamzah and Mohd Izuddin Mohamad - Razak, Faez; Hamzah, Hazralika; Mohamad, Mohd Izuddin (2009)
As introduced by its title "The Discretionary Powers of The YDPA: Its Significance and Workability in the Malaysian Government", this project paper accumulates the discretionary powers of the Yang di-Pertuan Agong entrenched in the Malaysian Federal Constitution. Hence, determining its significance and workability in the Malaysian government. This research is done out of the proposition that the YDPA as a mere nominal head of the States. The objectives are of two: First, to determine the extend of his discretionary powers entrenched in Malaysian highest authority of Federal Constitution and second, to come up with the significance of his role through his discretionary powers to the workability of the Malaysian government to show that he is not just a mere symbol. Consequently, several discretionary powers have been identified. Firstly, the power to appoint the Prime Minister, secondly, the withholding of consent to a request for Parliament's dissolution, third, powers to convene the meeting of the Conference of Rulers, fourthly, powers to declare emergency, fifth, powers to grant pardon and finally, other residual and implied discretionary powers. As the research is done pertaining to these powers, the YDPA's significance is indeed apparent to the workability of the Malaysian governmental system. This can be deduced from the fact that, the YDPA is evidently regarded as someone who provides check and balance, as a mediator to the constitutional dispute and on certain points cater to the sociological needs of the public.